Transmission Attributes of Periurban Malaria in Lusaka, Zambia, Precedent to the Integrated Vector Management Strategy: An Entomological Input - Emmanuel Chanda; Kumar S. Baboo; Cecilia J. Shinondo (Journal of Tropical Medicine)
Globalization and urbanization with their inherent developmental activities and ecological transformations impact on malaria epidemiology. Entomological factors involved in malaria transmission in periurban Lusaka were assessed prior to vector control reintroduction. Data was collected through standard entomological and epidemiological protocols and a pretested structured questionnaire. Larval habitats were characterized as transient (43%), semipermanent (36%), and permanent (21%). Anopheles arabiensis and An. gambiae ss. were the only vectors identified. A shift in vector population was noted, with the later outnumbering the former. Plasmodium falciparum monoinfection rates were 25.6% (95% CI: 20.9–30.7) (n=297). Parasitaemia was 31.8% (95% CI: 23.2–42.2), 25.7% (95% CI: 13.5–41.3), and 23.3% (95% CI: 17.4–29.6) in under 5, 5 to 14, and above 15 age groups, respectively. Low knowledge levels on vector control tools with an average of 7 residents per household were also observed. This study confirmed a local malaria transmission paradigm. The epidemiology necessitated deployment of an integrated vector management strategy with intensified information education and communication.